2021
DOI: 10.1186/s43058-021-00125-w
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of prostate cancer treatment decision aid in Michigan: a qualitative study

Abstract: Background The American Urological Association White Paper on Implementation of Shared Decision Making (SDM) into Urological Practice suggested SDM represents the state of the art in counseling for patients who are faced with difficult or uncertain medical decisions. The Michigan Urological Surgery Improvement Collaborative (MUSIC) implemented a decision aid, Personal Patient Profile-Prostate (P3P), in 2018 to help newly diagnosed prostate cancer patients make shared decisions with their clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The differences in clinicians' perspectives on use of decision aids in urology may explain the variation in urologists' effect on their use. 7,15,22 On multivariable analyses of data from the American Urological Association's Annual Census, we found that urologists' level of training, practice environment, and clinical volume influenced self-reported shared decision making and decision aid use. 7 In a similar study of Dutch practitioners caring for patients with metastatic castrate resistant PCa, de Angst et al found that less than half of urologists stated that a decision aid is appropriate for treatment decisions when patients have a choice between 2 or more treatment options.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The differences in clinicians' perspectives on use of decision aids in urology may explain the variation in urologists' effect on their use. 7,15,22 On multivariable analyses of data from the American Urological Association's Annual Census, we found that urologists' level of training, practice environment, and clinical volume influenced self-reported shared decision making and decision aid use. 7 In a similar study of Dutch practitioners caring for patients with metastatic castrate resistant PCa, de Angst et al found that less than half of urologists stated that a decision aid is appropriate for treatment decisions when patients have a choice between 2 or more treatment options.…”
Section: Discussionmentioning
confidence: 93%
“…One reason for the divergence in physician engagement with decision aids may be that despite strong evidence to support that decision aids improve several patient centered metrics (decisional regret, knowledge), these metrics may not align with outcomes that clinicians traditionally value (health outcomes). 7,15,25 Efforts to evaluate the impact of shared decision making and decision aid use on health outcomes beyond decisional impact may increase clinician engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step : Primary analyst coding Within 24-72 hours after the interview, the primary analyst codes the interview notes to the appropriate TICD determinants in the Microsoft Word TICD template (Appendix 2) (17,25,30). The primary analyst uses comments within Microsoft Word to flag sections to discuss during the consensus meeting with the secondary analyst.…”
Section: Tablementioning
confidence: 99%
“…Following the publication of the original article [ 1 ] the authors requested to update the “Competing interests” section as follows:…”
mentioning
confidence: 99%